Using Instructional Supervision to Improve Learners’ Performance in Eswatini High Schools - Naboth Mudavanhu Phebeni; Phumuzani Mpofu (E-Journal of Humanities, Arts and Social Sciences)
The primary objective of this study was to determine how instructional leadership is being used empirically in Eswatini and to establish whether it significantly impacts the performance of high school learners. This research employed a qualitative research methodology to gather data for the investigation. The sample comprised five principals and five deputy principals of five high schools in the Mbabane Hhohho Region, Eswatini. The qualitative data was analyzed using thematic analysis. Weber’s instructional leadership model guided the study’s theoretical framework. From the first research question, the findings revealed that instructional leadership improves school performance, provides adequate support structures for learners, helps manage school resources, and helps monitor and evaluate teaching and learning. The study suggested strategies that instructional supervisors can use to improve student performance by monitoring Curriculum and Instruction, collaborative leadership, and contextualizing instructional practices. Improving communication within the school and encouraging continuous professional development and parent involvement can also be helpful. The study concluded that instructional supervision is not effectively practiced in Eswatini schools. Therefore, the study recommends the appointment of principals on merit, parental involvement, and continuous staff development for principals. The study adds to the body of knowledge on instructional supervision in Eswatini. Several principals are unaware of instructional supervision in Eswatini, and in cases where they are, its implementation is minimal and does not fully constitute instructional supervision. School inspectors are informed on the part of the policy that guides instructional supervision in schools.